Helping the Medicare Population - Breese, Katie (My University, 2016)
This report will briefly detail a field experience completed at Riley County Extension office under the supervision of the director Jennifer Wilson and preceptor Virginia Barnard, MPH. The scope of the work involved tasks related to Medicare. The primary number of hours were spent counseling the Medicare population on Part D prescription drug plan choices.
Keywords: Medicare; SHICK; Riley County Extension